STUDI PERBANDINGAN MORALITAS MENGGUNAKAN MODEL TC DAN NHT DENGAN MEMPERHATIKAN KONSEP DIRI - Astika Kusni Wendhari; edi purnomo; yon rizal (JEE (Jurnal Edukasi Ekobis), 2022)
A problem in this research was low morality of students in the lessons integrated social class grade students oddVIIIthe first half of the public junior high schools 2 pesawaran.The research results show: ( 1 ) there is a difference in morality of students in learning integrated social class between the student with a model ly and nht, ( 2 ) morality of students in learning where social class integrated model ly higher than the nht on self-concept students a positive ( 3 ) morality of students in learning integrated social class where ly lower than nht on self-concept students negative ( 4 ) there are the influence of an interaction between kind of classroom with self-concept students on integrated learning social class and, ( 5 ) there is a difference in the average the results of morality between students who have self-concept positive and self-concept negative.Masalah dalam penelitian ini adalah rendahnya moralitas siswa pada pelajaran IPS Terpadu siswa kelas VIII Semester ganjil SMP Negeri 2 Pesawaran. Hasil penelitian menunjukkan: (1) ada perbedaan moralitas siswa dalam pembelajaran IPS Terpadu antara siswa dengan model TC dan NHT, (2) moralitas siswa dalam pembelajaran IPS Terpadu dimana model TC lebih tinggi dibandingkan dengan NHT pada konsep diri siswa yang positif, (3) moralitas siswa dalam pembelajaran Ips Terpadu dimana TC lebih rendah dibandingkan NHT pada konsep diri siswa negatif , (4) ada pengaruh interaksi antara model pembelajaran dengan konsep diri siswa pada pembelajaran IPS Terpadu dan , (5) Ada perbedaan rata-rata hasil moralitas antara siswa yang memiliki konsep diri positif dan konsep diri negatif.Kata kunci: moralitas, konsep diri, TC,